Trajectory‐Based Co‐Localization Measures for Nanoparticle‐Cell Interaction Studies. Issue 17 (15th December 2014) - Varela, Juan A.; Åberg, Christoffer; Simpson, Jeremy C.; Dawson, Kenneth A.
<x xml:space="preserve">Abstract</x> High‐resolution live cell microscopy will soon have a fundamental role in understanding bio‐nano interactions, providing material that can be exploited using single particle tracking techniques. The present work uses 3D timelapse images obtained with confocal microscopy, to temporally resolve the co‐localization between polystyrene nanoparticles and lysosomes in live cells through object‐based measurements.